2010
DOI: 10.1007/s11060-010-0143-7
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 clinical trial of bortezomib in adults with recurrent malignant glioma

Abstract: Bortezomib selectively binds and inhibits the 20S proteasome enzyme’s active sites. This study was conducted to determine the side effects and maximum tolerated dose (MTD) of bortezomib in patients with recurrent malignant glioma. Separate dose escalations were conducted in patients taking or not taking enzyme-inducing anti-seizure drugs (+/−EIASD). The starting dose in both groups was 0.9 mg/m2 intravenously twice weekly for the first three of each 4 week cycle. Imaging assessment of response was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 50 publications
2
64
0
Order By: Relevance
“…It has been shown that with the degradation of IκB, the NF-κB complex translocates into the nucleus thereby stimulating specific gene expression, survival factors, and insulin-like PFS-6 was 56 % with a best response of stable disease (SD). In another phase I trial in recurrent MG, treatment was given on days 1, 4, 8 and 11 of weeks 1 and 2 of a 3 week cycle with an MTD of 1.7 mg/m 2 in patients not on EIAEDs [25]. The median OS was 5.8 months with a PFS-6 of 9 % for patients on EIAEDs and 6 months and PFS-6 of 21 % if not on EIAEDS.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that with the degradation of IκB, the NF-κB complex translocates into the nucleus thereby stimulating specific gene expression, survival factors, and insulin-like PFS-6 was 56 % with a best response of stable disease (SD). In another phase I trial in recurrent MG, treatment was given on days 1, 4, 8 and 11 of weeks 1 and 2 of a 3 week cycle with an MTD of 1.7 mg/m 2 in patients not on EIAEDs [25]. The median OS was 5.8 months with a PFS-6 of 9 % for patients on EIAEDs and 6 months and PFS-6 of 21 % if not on EIAEDS.…”
Section: Discussionmentioning
confidence: 99%
“…243 These include mTOR inhibitors (temsirolimus, 244,245 everolimus 246 and AP23573), bortezomib 247,248 and protein kinase C (PKC) inhibitors. 229 Of particular interest in this group is enzastaurin (Eli Lilly, Indianapolis, IN, USA) which is a selective PKCb inhibitor.…”
Section: Intracellular Kinase Inhibitorsmentioning
confidence: 99%
“…Additionally a recent phase I trial in which bortezomib was used in glioblastoma patients seems to confirm this. 8 Finally, at a more recent follow-up, 1 of our patients (treated with bortezomib-dexamethasone and radiotherapy), was still alive at 50 months from diagnosis.…”
mentioning
confidence: 74%